2018
DOI: 10.1111/ijlh.12911
|View full text |Cite
|
Sign up to set email alerts
|

Usability of femoral head bone marrow to verify reference ranges for the assessment of myelodysplasia by flow cytometry

Abstract: Bone marrow samples from femoral heads are appropriate for verification of the proposed reference cutoff values of the individual parameters. Proposed reference cutoff values needed to be adjusted for reliable interpretation. Standardization of both data acquisition and data analysis is necessary for obtaining uniform results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…The Ogata scores with a cut‐off ≥2 have diagnostic and prognostic values (Della Porta et al, 2012 ; Della Porta et al, 2014 ). Scores of 2 are observed relatively often in patients with non‐clonal cytopenias, while scores 3 or 4 are significantly associated with cytomorphological myelodysplasia and MDS or MDS/MPN diagnosis (Rajab & Porwit, 2015 ; van Gammeren et al, 2018 ).…”
Section: Minimal Requirements To Assess Dysplasia By Mfcmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ogata scores with a cut‐off ≥2 have diagnostic and prognostic values (Della Porta et al, 2012 ; Della Porta et al, 2014 ). Scores of 2 are observed relatively often in patients with non‐clonal cytopenias, while scores 3 or 4 are significantly associated with cytomorphological myelodysplasia and MDS or MDS/MPN diagnosis (Rajab & Porwit, 2015 ; van Gammeren et al, 2018 ).…”
Section: Minimal Requirements To Assess Dysplasia By Mfcmentioning
confidence: 99%
“…Initially, a fourth DC subset, slanDC, was identified based on the expression of M-DC8 (6-sulfo LacNAc or slan) and CD16. Further studies showed that these SLAN+ cells are more closely related to monocytes than to DC and they were renamed as slan+ nc monocytes (van Leeuwen-Kerkhoff et al, 2017;2018). A decrease in the specific slan+ ncMo subset and increased CD1c + cDC (Meyerson et al, 2016) are features of CMML but their use in the diagnosis or prognostication of MDS is unclear (Van Leeuwen-Kerkhoff et al, 2021).…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…We demonstrate the femoral heads removed during THA provide abundant functional mononuclear and CD34 + cells as controls. A previous study reported on the utility of femoral head bone marrow for verification of cutoffs in flow cytometry evaluation of myelodysplastic syndromes [8]. Another study compared iliac crest, vertebral body, and femoral head MNCs as a source of mesenchymal stromal cells [9].…”
Section: Discussionmentioning
confidence: 99%
“…To identify alternative sources of hematopoietic cells as controls for studies of adult leukemia, we piloted the use of bone marrow cells extracted from the femoral heads of patients requiring elective total hip arthroplasty (THA). While we are not the first to use hematopoietic cells derived from femoral heads for laboratory studies [7][8][9], we are the first to report the abundances of cells derived from this unique source. We demonstrate that sufficient cells are recovered to perform functional studies, justifying the investment of time and resources required to establish the logistics.…”
Section: Introductionmentioning
confidence: 99%